Isolation of nitrate-reducing bacteria from an offshore reservoir and the associated biosurfactant production. Issue 47 (25th July 2018) - Fan, Fuqiang; Zhang, Baiyu; Morrill, Penny L.; Husain, Tahir
Abstract : Biosurfactant producing nitrate-reducing bacteria (NRB) in anaerobic reservoir environments are closely associated with souring (H2 S) control in the offshore oil and gas industry. Abstract : Biosurfactant producing nitrate-reducing bacteria (NRB) in anaerobic reservoir environments are closely associated with souring (H2 S) control in the offshore oil and gas industry. Five NRB strains were screened from offshore produced water samples and all were identified as Pseudomonas stutzeri . Their biosurfactant producing abilities when fed on either glucose or glycerol media were investigated. P. stutzeri CX3 reduced the medium surface tension to 33.5 and 29.6 mN m −1, respectively, while growing on glucose or glycerol media. The CX3 strain was further inoculated to examine its growth performance, resulting in 32.4% and 94.5% of nitrate consumption over 228 hours of monitoring in two media, respectively. The composition analysis of the biosurfactant product generated by P. stutzeri CX3 was conducted through thin-layer chromatography, gas chromatography with a flame ionization detector (FID) and Fourier transform infrared spectroscopy (FT-IR). The biosurfactant product was identified as a mixture of a small part of lipopeptides and a large part of glycolipids while its critical micellar concentration (CMC) was as low as 35 mg L −1 . The biosurfactant product demonstrated high stability over a wide range of temperature (4–121 °C), pH (2–10), and salinity (0–20% w/v) concentration. The results provided valuable technical and methodological support for effective offshore reservoir souring control and associated enhanced oil recovery activities.